Relations between the European Union and the African, Caribbean and Pacific Group of States: current state and prospects (Economic and Political Thought, 2018)
The relations between the European Union (EU) and the African, Caribbeanand Pacific Group of States (ACP) are an example of an extremelydeveloped model of the EU cooperation with developing countries. Over the60-year period, it has been governed by many agreements establishing specialforms of relations between the parties, creating its own institutional systemof these relations, mechanisms of financial support and trade exchange. Currently,the reciprocal relations are maintained on the basis of the PartnershipAgreement, concluded on 23 June 2000 in Cotonou. Its assumptions, however,expire on 29 February 2020, and the approaching end of the CotonouAgreement raises questions about the future of the relations between the EUand the ACP group. Firstly, The article focuses on discussing the current stateof implementation of the Cotonou Agreement, in particular the dimension oftrade and economic cooperation since it will determine the most importantfuture negotiations between the EU and the ACP group. Secondly, the articleis based on the analysis of unofficial negotiation positions of both the EUand the ACP group, the separateness of which is so important that it doesnot bode well for conversations scheduled to start in 2018.
Keywords: European Union, Africa, the Caribbean, the Pacific, ACP